The Role Of Keimin Bunka Shidosho In The Dynamics Of Art In Indonesia 1943-1945 - Masriyani, Siti; Azizah, Nurul (Siginjai: Jurnal Sejarah, 2025)
This research discusses the role of the Keimin Bunka Shidosho (KBS) institution during the Japanese occupation in Indonesia, particularly in the realm of arts and culture. KBS, established by the Japanese government, aimed to use art as a tool of propaganda to support Japanese interests. Various art forms, such as literature, painting, music, drama, and film, underwent significant changes under the influence of KBS. This study uses the historical research method, which involves four key stages: heuristics, source criticism, interpretation, and historiography. Through this method, the research investigates how artists navigated the tension between political control and creative expression. This research is important in understanding how cultural institutions were used to influence public sentiment and how artists responded to ideological pressure. The urgency lies in examining how, even under occupation and censorship, art became a space for negotiation, resistance, and the assertion of national identity. The findings show that while some artists worked within the framework of KBS, others resisted or embedded nationalist messages in their works. As a result, art during the Japanese occupation not only functioned as a propaganda tool but also as a means to foster resistance and national pride